1998
DOI: 10.1109/78.705427
|View full text |Cite
|
Sign up to set email alerts
|

Parameter estimation of two-dimensional moving average random fields

Abstract: Index Terms-Maximum likelihood, moving average random fields, parameter estimation, random fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…To compute a value inside the volume, it is sufficient to identify the appropriate slices to which the point belongs at each level of this decomposition and then to compute the value of the residual texture inside the volume. For this purpose, modelling of residual texture as a 3Dl moving average field (Francos and Friedlander, 1998;Ojeda et al, 2010) is employed with calibrating the results to the observed statistics on the boundary of the borehole. Autocorrelations of this field are evaluated by its boundary values and are used for continuation of the field inside the volume.…”
Section: Description Of the Methodsmentioning
confidence: 99%
“…To compute a value inside the volume, it is sufficient to identify the appropriate slices to which the point belongs at each level of this decomposition and then to compute the value of the residual texture inside the volume. For this purpose, modelling of residual texture as a 3Dl moving average field (Francos and Friedlander, 1998;Ojeda et al, 2010) is employed with calibrating the results to the observed statistics on the boundary of the borehole. Autocorrelations of this field are evaluated by its boundary values and are used for continuation of the field inside the volume.…”
Section: Description Of the Methodsmentioning
confidence: 99%
“…Once the phase parameters were estimated, the random amplitude of the polynomial phase signal is obtained by multiplying the observed signal by , where is the estimated phase. Since is a homogeneous random field, its parameters can be estimated using any standard algorithm (see, e.g., [14] for the case where is an autoregressive field and [16] for the case where is a moving-average field).…”
Section: A Estimation Procedures For a Nonzero Mean Amplitude Fieldmentioning
confidence: 99%
“…Thus, closed-form formulas for the CRB are obtained by substituting into the expression for the amplitude field covariance matrix, which is expressed in terms of the amplitude field parameters. As an example, the expression for the covariance matrix of a nonsymmetric half-plane 2-D moving average field is derived in [16].…”
Section: B Derivation Of the Crbmentioning
confidence: 99%
See 1 more Smart Citation
“…Many problems are related to not only the one dimensional (1-D) stochastic systems but also the two dimensional (2-D) stochastic systems since it is important for many engineering problems to study the stochastic 2-D systems, such as the signal processing, the image processing, the azimuth estimation of planar surface, the uniform texture processing, analysis of earthquake wave and the soil mechanics and so on [16][17][18][19][20][21][22][23][24][25][26][27][28]. For example, we have the 2-D Wold-like decomposition in the uniform texture processing [10].…”
Section: Introductionmentioning
confidence: 99%